Exploration of resistance mechanisms for epidermal growth factor receptor‐tyrosine kinase inhibitors based on plasma analysis by digital polymerase chain reaction and next‐generation sequencing. Issue 12 (13th November 2018) - Iwama, Eiji; Sakai, Kazuko; Azuma, Koichi; Harada, Daijiro; Nosaki, Kaname; Hotta, Katsuyuki; Nishio, Makoto; Kurata, Takayasu; Fukuhara, Tatsuro; Akamatsu, Hiroaki; Goto, Koichi; Shimose, Takayuki; et al.
Abstract : Liquid biopsy offers a potential alternative to tissue biopsy for detection of genetic alterations in cancer, and it has been introduced into clinical practice to detect the tyrosine kinase inhibitor (TKI) resistance‐conferring T790M mutation of epidermal growth factor receptor ( EGFR ) in patients with non‐small‐cell lung cancer (NSCLC). We prospectively collected tumor and plasma samples from 25 NSCLC patients who harbored activating mutations of EGFR and experienced failure of treatment with afatinib. The samples were analyzed by digital PCR (dPCR) and next‐generation sequencing (NGS). T790M was detected in plasma with a respective sensitivity and specificity of 83.3% and 70.0% by dPCR and 50.0% and 70.0% by NGS relative to analysis of corresponding tumor samples. Quantitation of T790M based on the ratio of the number of T790M alleles to that of activating mutation alleles (T/A ratio) improved the specificity of plasma analysis to 100% for both dPCR and NGS without a reduction in sensitivity. Although several afatinib resistance mechanisms other than T790M—including copy number gain of NRAS or MET —were identified in tumor samples, the corresponding genetic alterations were not detected in plasma. TP53 mutations were frequently identified in plasma and tumor samples, with most such mutations also having been detected before afatinib treatment. The presence of de novo TP53 mutations was associated with reduced progression‐free survival. Quantitation of T790M in plasma is thus a clinically relevant approach to determine the T790M status of tumors. In addition, genetic alterations coexisting with EGFR mutations can affect the efficacy of EGFR‐TKI treatment. Abstract : Quantitation of T790M in plasma is a clinically relevant approach to determine the T790M status of tumors.